2016
DOI: 10.1002/dmrr.2694
|View full text |Cite
|
Sign up to set email alerts
|

The 2015 IWGDF guidance documents on prevention and management of foot problems in diabetes: development of an evidence‐based global consensus

Abstract: Foot problems complicating diabetes are a source of major patient suffering and societal costs. Investing in evidence-based, internationally appropriate diabetic foot care guidance is likely among the most cost-effective forms of healthcare expenditure, provided it is goal-focused and properly implemented. The International Working Group on the Diabetic Foot (IWGDF) has been publishing and updating international Practical Guidelines since 1999. The 2015 updates are based on systematic reviews of the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
304
0
32

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 338 publications
(339 citation statements)
references
References 27 publications
3
304
0
32
Order By: Relevance
“…Therefore, it's necessary to prevent its occurrence by a systematic foot examination. This examination allows an assessment of the foot risk and the screening of early lesions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it's necessary to prevent its occurrence by a systematic foot examination. This examination allows an assessment of the foot risk and the screening of early lesions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Частота и тяжесть заболеваний стопы различают-ся в разных регионах мира, главным образом вслед-ствие различных социально-экономических условий, обеспеченности особыми типами обуви и стандар-тами осуществления специализированной помощи [1]. Язвенные поражения стопы являются наиболее частой проблемой и характеризуются заболеваемо-стью около 2-4 % в год в развитых странах и даже выше в развивающихся странах [2].…”
Section: Manual and Documents Of International Working Group On The Dunclassified
“…Recent clinical studies have demonstrated that in the presence of a clinically infected ulcer, a positive PTB test is highly suggestive of osteomyelitis, but a negative test does not rule out the diagnosis; conversely, in the situation of an apparently uninfected foot wound, a positive PTB test is not specific for osteomyelitis, but this diagnosis is unlikely if the PTB test is negative. [19][20][21][22][23][24][25] This clinical sign is of great importance since early reports in 1995, Grayson et al 16 who explored the possibility of osteomyelitis in wounds by the use of a sterile blunt metal probe. They concluded that the PTB test had a positive predictive value of 89%.…”
Section: -14 Days)mentioning
confidence: 99%
“…31 Furthermore, recently the International Working Group on Diabetic Foot Management (IWGDF) has warned against the use of topical antimicrobial dressing with the goal of improving wound healing or preventing secondary infection. 20 They went even further by saying that "currently supporting data are too limited to recommend topical antimicrobial therapy". [20][21][22] The use of antimicrobial dressings for DFUs was recently assessed via a systemic review which concluded that current evidence base is too weak to suggest any specific antimicrobial dressing.…”
Section: -14 Days)mentioning
confidence: 99%
See 1 more Smart Citation